FROM BRAND BUILDING TO REVENUE GROWTH: AI-ENABLED STRATEGIC PATHWAYS FOR SCALING MODERN MARKETING ORGANIZATIONS - RATNAYAKE, DINETH (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The increasing demand for measurable business impact has transformed marketing from a brand-centric function into a revenue-driven growth engine. This study investigates how AI-enabled strategic pathways facilitate the transition from traditional brand building to scalable revenue growth in modern marketing organizations. Adopting an explanatory sequential mixed-method design, the research integrates survey-based quantitative analysis with structural equation modeling, hierarchical regression, and cluster profiling to examine the relationships among Brand Equity Strength, AI Capability Maturity, Customer Intelligence Integration, Marketing–Sales Alignment, Operational Agility, and Revenue Growth Rate. The findings reveal that while brand equity significantly contributes to performance, AI Capability Maturity emerges as the strongest predictor of revenue growth, both directly and indirectly through Customer Intelligence Integration. Hierarchical regression models demonstrate substantial incremental explanatory power as AI and agility variables are introduced, with the final model explaining 76% of revenue variance. Cluster analysis further highlights a clear performance gradient, with AI-Native organizations significantly outperforming Traditional firms. The results confirm that revenue scaling is not merely a function of branding excellence but of integrated technological, strategic, and organizational capabilities. The study concludes that AI-enabled intelligence architectures, combined with agile execution and cross-functional alignment, constitute essential strategic pathways for achieving sustainable enterprise growth in contemporary marketing ecosystems